(untitled) (Економіка і регіон/ Economics and region, 2024)
The article examines the conceptual foundations and evolution of state regulation of food industry enterprises in Ukraine. Within the framework of the conducted research, the evolution of state regulation in Ukraine was considered. Based on the main provisions of the Constitution of Ukraine, the analysis of scientific sources and publications, the definition of the concept of "state regulation" was formed. Information on the evolution of state regulation of the food industry in Ukraine has been systematized and presented. According to the results of the conducted research, the main elements of evolution and the conceptual foundations of state regulation of food industry enterprises in Ukraine were determined. The key shortcomings and ways to improve the state regulation of food industry enterprises in Ukraine have been identified. The prospects for the development of conceptual foundations and the evolution of state regulation of food industry enterprises in Ukraine have been determined.